The people vs. Alex Cross [compact disc, unabridged] - Patterson, James, 1947- (Patterson, James, 1947- Alex Cross series., 2017)
Alex Cross is on the wrong side of the law. Serving a suspension from the force while he awaits trial for murder, Cross has been branded as a trigger-happy cop, another bad apple walking the streets with a gun, an accusation that Cross will do anything to refute. To make himself feel useful again, Cross opens a counseling office in the basement of his home. When his former partner Sampson shows up needing his help, Cross jumps at the chance, even if it may end up costing him what's left of his career. When a string of young, blonde women go missing, the investigation leads Cross and Sampson to the most depraved, darkest corners of the internet.